1994
DOI: 10.1086/418744
|View full text |Cite
|
Sign up to set email alerts
|

The Island Syndrome in Rodent Populations

Abstract: Populations of rodents isolated on islands often show systematic differences in demography, reproduction, behavior, and morphology when compared to mainland populations. These differences, termed the island syndrome, include higher and more stable densities, better survival, increased body mass, and reduced aggressiveness, reproductive output, and dispersal. We synthesize information in the literature on island rodent populations and construct a conceptual model to explain the island syndrome. Population densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
409
6
25

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 425 publications
(469 citation statements)
references
References 109 publications
15
409
6
25
Order By: Relevance
“…Ship rats on islands were heavier and larger (Yom-tov et al 1999) than on mainland New Zealand which supports the micro-evolutionary portion of the theory, probably because a large suite of competitors and predators were absent (Adler & Levins 1994;Yom-tov et al 1999;Ventura & Lopez Fuster 2000). Rapid morphological responses in rodents and other small mammals to changing ecological conditions are now well recorded (Pergams & Ashley 2001;Pergams & Lawyer 2009;Cucchi et al 2014).…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Ship rats on islands were heavier and larger (Yom-tov et al 1999) than on mainland New Zealand which supports the micro-evolutionary portion of the theory, probably because a large suite of competitors and predators were absent (Adler & Levins 1994;Yom-tov et al 1999;Ventura & Lopez Fuster 2000). Rapid morphological responses in rodents and other small mammals to changing ecological conditions are now well recorded (Pergams & Ashley 2001;Pergams & Lawyer 2009;Cucchi et al 2014).…”
Section: Discussionmentioning
confidence: 63%
“…As the population ecology of island rodents may differ from that of continental populations (Gliwicz 1980;Adler & Levins 1994;Polis et al 1997) understanding the responses of rats to island ecosystems will assist with their management. There is evidence for increased population densities, larger body sizes and reduced reproductive rates in rodents on islands (Key et al 1998;Innes 2005), which have been attributed to the 'island syndrome' (Adler & Levins 1994;Russell et al 2011b) as a response to reduced dispersal, competition and predation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…nivalis is one of the most common mustelids occurring in the islands of the Palaearctic region, inhabiting all Mediterranean islands larger than 240 km 2 with the exception of Ibiza and Cyprus (Masseti, 1995;De Marinis and Masseti, 2003). As is often reported for small mammals (Blondel and Vigne, 1993;Alder and Levins, 1994;Michaux et al, 2002), insular and mainland populations of M. nivalis differ morphologically. These variations include larger body size and darker coat colouration in insular populations (Beaucournu and Grulich, 1968;Alcover and Jaume, 1983) and led to the description of potentially one subspecies per island (Beaucournu and Grulich, 1968;De Marinis, 1996).…”
Section: Introductionmentioning
confidence: 96%
“…We predicted that fewer mice would move from the forest edge to the agricultural fields surrounding smaller than larger forest patches, but our results did not support the inhibited dispersal hypothesis. Diaz et al (1999) found no difference in movements of Apodemus sylvaticus to the exterior in relation to patch size, whereas Krohne and Hoch (1999) found that P. leucopus populations in Indiana had lower dispersal rates from smaller patches, a factor that may have resulted in higher densities in those patches (Adler and Levins 1994). Nupp and Swihart (1996) concluded that both reduced dispersal and greater abundances of food contributed to the high densities of P. leucopus they observed in small forest woodlots.…”
Section: Patch Sizementioning
confidence: 97%